Multidisciplinary management of cleidocranial dysplasia - Literature review with meta-analysis (Research, Society and Development, 2023)
Introduction: The article in question explains a literature review, clearly presenting Cleidocranial Dysplasia (CCD), in a dental and medical view. Above all, indicating its main clinical manifestations and concomitantly with this, we elucidate an approach through general diagnosis and a dental diagnosis. Objectives: It aims to show how early investigation leads to a good prognosis, highlighting pre- and postnatal care as a decisive factor and, therefore, identifying changes in dysplasia in clinical and complementary exams. Methodology: The article is a literature review with a quali-quantitative approach and meta-analysis. The bibliographical survey was carried out in the databases of Google Scholar, PUBMED and Scielo, in English and Portuguese. The selected articles were those that addressed the theme and had been published in the last ten years. Results: A total of fifteen articles were found. These were subjected to a deep analysis and observed if the subject approached matches the one recommended by the study, obeying the exclusion criteria. Final considerations: Prenatal and postnatal care of patients with the syndrome is necessary to have a predictability of possible skeletal, orodental and orofacial manifestations due to the genetic mutation of RUNX2. In the face of these issues, normally the first professional to be sought is the DSS (Doctor of Dental Surgery), due to the delay in the eruption of the permanent dentition, with late diagnosis being the result of a multidisciplinary association of treatment involving psychologists, doctors of dental surgery, physicians, physiotherapists, speech-language pathologist, nursing team and community agent.